A New PKD1 Mutation Discovered in a Chinese Family with Autosomal Polycystic Kidney Disease - Zhendi Wang; Yang Wang; Jing Xiong (Karger Publishers, 2014)
Background/Aims: Autosomal-dominant polycystic kidney disease (ADPKD), a heterogeneous genetic disorder characterized by massive kidney enlargement and progressive chronic kidney disease, is due to abnormal proliferation of renal tubular epithelium. ADPKD is known to be caused by mutations in PKD1 and PKD2 genes. Methods: In the present study, the mutation analysis of PKD genes was performed in a new Chinese family with ADPKD using Long-Range (LR) PCR sequencing and targeted next-generation sequencing (targeted DNA-HiSeq). Results: A unique 28 bp deletion (c.12605_12632del28) in exon 46 of the PKD1 gene was identified in two affected family members by LR PCR method, but not in any unaffected relatives or unrelated controls. Higher accuracy and less missing detection presented in LR PCR method compared with targeted DNA-HiSeq. This mutation c.12605_12632del28 (p.Arg4202ProextX146) resulted in a delayed termination of amino acid code, and was highly speculated pathogenic in this ADPKD family. Moreover, this newly identified frame-shift change was compared to the PKD gene database, but no similar mutation was yet reported. Conclusion: A novel frame-shift mutation, c. 12605_12632del28, in the PKD1 gene was found in a Chinese ADPKD family. All evidence available suggested that it might be the mutation responsible for the disease in that family.